2001
DOI: 10.1006/viro.2001.0960
|View full text |Cite
|
Sign up to set email alerts
|

Deletion and Substitution Analysis Defines Regions and Residues within the Phosphoprotein of Bovine Respiratory Syncytial Virus That Affect Transcription, RNA Replication, and Interaction with the Nucleoprotein

Abstract: The phosphoprotein (P) of bovine respiratory syncytial virus (BRSV) is a multifunctional protein that plays a central role in transcription and replication of the viral genomic RNA. To investigate the domains and specific residues involved in different activities of the P protein, we generated a total of 22 deletion and 17 point mutants of the P protein. These mutants were characterized using an intracellular BRSV-CAT minigenome replication system for the ability to (1) direct minigenome transcription, (2) dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 42 publications
0
10
0
1
Order By: Relevance
“…The P protein is a homotetramer which interacts with N (Garcia-Barreno et al, 1996), L (Khattar et al, 2001), and M2-1 (Asenjo et al, 2006) and which is an essential co-factor of the polymerase. Although much shorter than other Paramyxoviridae counterparts, RSV P has similar activities.…”
Section: Virus Rnas and Proteinsmentioning
confidence: 99%
“…The P protein is a homotetramer which interacts with N (Garcia-Barreno et al, 1996), L (Khattar et al, 2001), and M2-1 (Asenjo et al, 2006) and which is an essential co-factor of the polymerase. Although much shorter than other Paramyxoviridae counterparts, RSV P has similar activities.…”
Section: Virus Rnas and Proteinsmentioning
confidence: 99%
“…Studies of the P protein of bovine RSV, a homologue of human RSV, also showed that the C-terminal end and an internal region between residues 161 to 180 are required for N-P complex formation by coimmunoprecipitation analysis (30,28). Moreover, deletion studies of the bovine RSV P protein shows that only residues 41 to 80 could be removed without significantly impairing bovine RSV minigenome replication (27).…”
mentioning
confidence: 98%
“…The RNP complex isolated from RSV-infected cells has been shown to possess an RNAdependent RNA polymerase (RdRp), mRNA polyadenylation, and mRNA capping activities in vitro (4,5,27). Multiple protein-protein and protein-RNA interactions mediate the assembly and activity of this complex (12,13,16,20,21,26,33,38,41). Thus, the RSV RNP is a complex that is rich in potential antiviral targets.…”
mentioning
confidence: 99%